2017
DOI: 10.1038/s41598-017-06953-y
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 stabilises the processing intermediates of mitochondrial transcripts

Abstract: The 43-kDa trans-activating response region DNA-binding protein 43 (TDP-43) is a product of a causative gene for amyotrophic lateral sclerosis (ALS). Despite of accumulating evidence that mitochondrial dysfunction underlies the pathogenesis of TDP-43–related ALS, the roles of wild-type TDP-43 in mitochondria are unknown. Here, we show that the small TDP-43 population present in mitochondria binds directly to a subset of mitochondrial tRNAs and precursor RNA encoded in L-strand mtDNA. Upregulated expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 43 publications
0
56
1
Order By: Relevance
“…In the cortical neurons of transgenic mice, the mitochondrial association of mutant TDP-43 was stronger than the endogenous protein in nontransgenic littermates, suggesting that mutant TDP-43 has a higher tropism for mitochondria. A recent study has also proposed that WT TDP43 may serve a physiological function by stabilizing a subset of tRNAs and mRNA intermediates in mitochondria ( Izumikawa et al, 2017 ). However, unlike the studies mentioned above, in human fibroblasts harboring mutant TDP-43, a decrease in mitochondria membrane potential was detected in the absence of alterations in oxygen consumption and mitochondrial localization of TDP-43 ( Onesto et al, 2016 ).…”
Section: Mitochondrial Sod1 and Oxphos In Familial Alsmentioning
confidence: 99%
“…In the cortical neurons of transgenic mice, the mitochondrial association of mutant TDP-43 was stronger than the endogenous protein in nontransgenic littermates, suggesting that mutant TDP-43 has a higher tropism for mitochondria. A recent study has also proposed that WT TDP43 may serve a physiological function by stabilizing a subset of tRNAs and mRNA intermediates in mitochondria ( Izumikawa et al, 2017 ). However, unlike the studies mentioned above, in human fibroblasts harboring mutant TDP-43, a decrease in mitochondria membrane potential was detected in the absence of alterations in oxygen consumption and mitochondrial localization of TDP-43 ( Onesto et al, 2016 ).…”
Section: Mitochondrial Sod1 and Oxphos In Familial Alsmentioning
confidence: 99%
“…Similar changes in mitochondrial morphology and function are reported in models of ALS 39 , inclusion body myositis 51 , and Parkinson’s disease 52 . TDP-43 binds to and regulates the processing of transcripts encoding mitochondrial proteins 53 , 54 , and TDP-43 also contains a mitochondrial localizing sequence, leading to mitochondrial dysfunction upon cytoplasmic TDP-43 mislocalization 53 . Our results further emphasize mitochondrial abnormalities in ALS patient-derived cells, and highlight the deleterious effects of TDP-43 deposition on the metabolism of RNAs essential for oxidative phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…They provide energy and also participate in nearly all types of cell death, including apoptosis and necrosis, and contribute to a number of important physiological functions (Kroemer et al, 1998). Studies have shown that TDP-43 plays an important role in stabilizing mitochondrial function, and pathological TDP-43 can cause mitochondrial dysfunction (Izumikawa et al, 2017). Abnormal TDP-43 may cause mitochondrial dysfunction by affecting mitochondrial morphology, reactive oxygen species (ROS) generation, oxidative respiratory chain and localization.…”
Section: Tdp-43 and Mitochondrial Dysfunctionmentioning
confidence: 99%